Digital image forgery detection: a systematic scrutiny. Issue 5 (3rd September 2019) - Walia, Savita; Kumar, Krishan
Abstract: Image manipulation has eroded our trust of digital images, with more subtle forgery methods posing an ever-increasing challenge to the integrity of images and their authenticity. Over recent years, a significant research contribution has been dedicated to devising new techniques for countering various image forgery attacks. In this article, a survey of such research contributions has been conducted by following a well-defined systematic process. A total of 66 primary studies published before July 2017 was selected from five different electronic databases using a careful scrutinizing process. Four research questions have been formulated that capture various aspects of the identified primary studies. The field background required to understand the evolution of digital image forgeries is also presented. The aim of this systematic survey is to gain insights into the current research on the detection of these forgeries by comprehensively analysing the selected studies in order to answer this predefined set of research questions. This survey also discusses various challenges that need to be addressed, and has recommendations for possible future research directions.